Effect of assertive training on cyber bullying behavior for students - Farida Aryani; Muhammad Ilham Bakhtiar (Universitas Negeri Padang, 2018)
The purpose of this study was to determine the description of cyber bullying behavior in schools, to know the implementation of assertive training on cyber bullying behavior and to know the effect of assertive training on cyber bullying behavior before and after treatment. This research is quantitative using the true-experimental design approach. A sample of 31 people. The results of the study are; (1) almost all students have bullied or there are 32% where they do bullying such as taunting, tweaking, humiliating and posting it on the Internet, and students take steps to report to the teacher in the event of bullying or about 59% of students do it. (2) Assertive training activities on cyber bullying behavior carried out in 4 (four) sessions: introductions, assertive explanations, assertive behavior such as honest behavior, expressing thoughts and feelings, identifying behavior desired by clients and expectations, expressing ideas that irrational, attitudes and misunderstandings in the minds of clients / students. Communication skills and dare to say no through “Speak UP”. (3) From the result’s hypothesis, hypothesis, testing provision, assertive training is very influential on the behavior of bullying in schools. For experimental group and experimental group did not have a significant change.